Competence of Agricultural Extension An Effort To Increase Agricultural Productivity In Sidoarjo - Faisol Humaidi; Teguh Soedarto (Agricultural Science, 2022)
Sidoarjo Regency is one of the agricultural production areas, especially vegetables and is the largest supplier to Surabaya. The high productivity of agriculture cannot be separated from the role of agricultural extension workers who are spread in most sub-districts in Sidoarjo Regency. The purpose of this research is to measure the performance of agricultural extension workers in order to increase agricultural productivity, especially vegetables in Sidoarjo Regency. This research method uses descriptive, analytic and correlational approaches. A good extension policy strategy that can increase agricultural productivity is carried out by increasing programs related to institutions, quantity and quality of Agricultural Extension Officers and improving farmer group institutions. With this policy strategy, it can improve the quality of Agricultural Extension through education and training, as well as empowerment farmer groups by improving programs related to institutions, quantity and quality extension workers and institutional improvement of farmer groups. The results of the study show that the performance of Agricultural Extension Officers in the context of increasing agricultural productivity is in the very good category.